MEANING OF SYMBOLS IN RUMAH ADAT BOLON BATAK TOBA: A SEMIOTIC PERSPECTIVE - Herman; Dumaris E Silalahi; Swasty Lumbanraja (Sean Institute, 2022)
This research is to explain about various kinds of symbols, as well as the meaning of the symbols and the reasons why the use of each symbol in the Toba Batak Traditional House. The purpose of the research is to find out the types of symbols, and also the meaning of each symbols in the Toba Batak Traditional house and also the reasons of using symbols in the Toba Batak Traditional House. This research uses qualitative descriptive method. Toba Batak Traditional House in T.B Silalahi Center Balige is the source of the data obtained by the researcher was also clarified by several sources who were at the TB Silalahi Center. The result of this research is the symbols in Toba Batak Traditional House have meanings in symbolizing Tarus symbol as prosperity and mother’s love, Boraspati symbol as fertility, jenggar symbol as strength, Singa-singa symbol as prestigious, Ulupaung as wisdom, Gaja Dompak symbol as truth, Santung-santung symbol as truth and law, Simeol-eol and Simeol-eol Marsialoan symbols as happines and tolerance, Ipon-ipon symbol as beauty and harmony, Silintong symbolsas warmth, and Desa Na Ualu symbol as balance